2011
DOI: 10.1111/j.1365-2354.2010.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing genetic counselling for hereditary cancers: the client's perspective

Abstract: As genetic health care expands and genetic testing becomes more widely available, it becomes relevant to understand how individuals involved in genetic counselling are integrating this new information in health management and into their lives. This article examines the client's experiences of genetic counselling for hereditary cancers, which definitely play a major role in the assessment of their needs and also lead to improvement of the psychosocial focus in genetic counselling protocols. Methods include a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 10 publications
(15 reference statements)
1
30
0
2
Order By: Relevance
“…[26,27] Our participants also mentioned that they received inadequate written material, in line with findings that most women with breast or ovarian cancer were inadequately prepared because of lack of pre-information. [28] Moreover, they strongly believed that DCGs provided insufficient facilities for psychosocial support, like counselees with hereditary cancer in a previous study, which suggested that counselees should have opportunities to receive psychosocial support through the GC process [22] regardless of their educational background. Educational background is potentially relevant in this context as there are indications that counselors may propose psychological services to highly educated counselees more often than to others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[26,27] Our participants also mentioned that they received inadequate written material, in line with findings that most women with breast or ovarian cancer were inadequately prepared because of lack of pre-information. [28] Moreover, they strongly believed that DCGs provided insufficient facilities for psychosocial support, like counselees with hereditary cancer in a previous study, which suggested that counselees should have opportunities to receive psychosocial support through the GC process [22] regardless of their educational background. Educational background is potentially relevant in this context as there are indications that counselors may propose psychological services to highly educated counselees more often than to others.…”
Section: Discussionmentioning
confidence: 99%
“…This too is consistent with views of participants in another study, that creating a user-friendly website with informative and understandable language, and blogs for peer support, would be useful. [22] 4.1 Limitations Several limitations and strengths affect the trustworthiness of this study. The strengths include the size of the group of male BRCA1/2 mutation carriers that participated, and both the richness and saturation of the acquired data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As background to the study, we relied on literature about the effects of chronic illness on: family functioning [39,42], familial aspects of inherited risk [4,5,43,51], and prior research findings [52].…”
Section: Interview Guidementioning
confidence: 99%